Implementation of the Islamic Social Entrepreneurship Concept in the Pondok Modern Darussalam Gontor Business Unit: Implementasi Konsep Islamic Social Entrepreneurship pada Unit Usaha Pondok Modern Darussalam Gontor - Muhammad Agus Setiawan; Sheema Haseena Armina; Achmad Jalaludin (Institute of Advanced Knowledge and Science, 2024)
Islamic social entrepreneurship is a concept of social entrepreneurship based on Islamic principles and values. The goal is to create positive social impact and benefits for the wider community. This paper aims to analyze the application of the concept of Islamic social entrepreneurship in business units in Pondok Modern Darussalam Gontor. Gontor is the oldest Islamic educational institution in Indonesia known for its education system that prioritizes the independence and entrepreneurship of its students. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth observation and interviews. The results showed that Gontor has applied the concept of Islamic social entrepreneurship to business units such as printing, agriculture, animal husbandry, and others. The principles of tawhid, justice, partnership, and social responsibility are implemented in the management of these business units. The hope is that Gontor alumni can establish organizations or companies that provide broad benefits to society by adhering to Islamic ethics.